Expression of Fbp2, a Newly Discovered Constituent of Memory Formation Mechanisms, Is Regulated by Astrocyte–Neuron Crosstalk - Hajka, Daria (Int J Mol Sci, 2020)
Fbp2 (muscle isozyme of fructose 1,6-bisphosphatase) is a glyconeogenesis-regulating enzyme and a multifunctional protein indispensable for long-term potentiation (LTP) formation in the hippocampus. Here, we present evidence that expression of Fbp2 in murine hippocampal cell cultures is regulated by crosstalk between neurons and astrocytes. Co-culturing of the two cell types results in a decrease in Fbp2 expression in astrocytes, and its simultaneous increase in neurons, as compared to monocultures. These changes are regulated by paracrine signaling using extracellular vesicle (EV)-packed factors released to the culture medium. It is well accepted that astrocyte–neuron metabolic crosstalk plays a crucial role in shaping neuronal function, and recently we have suggested that Fbp2 is a hub linking neuronal signaling with redox and/or energetic state of brain during the formation of memory traces. Thus, our present results emphasize the importance of astrocyte–neuron crosstalk in the regulation of the cells’ metabolism and synaptic plasticity, and bring us one step closer to a mechanistic understanding of the role of Fbp2 in these processes.